A New Approach For Solving Integer Interval Transportation Problem With Mixed Constraints. (November 2019) - Keerthana, G.; Ramesh, G.
Abstract: In this paper, we suggest an interval Transportation problem where the source and destination parameters are chosen as interval numbers. The main objective of the problem is to minimize the total transportation cost and total delivery time. Algorithm is proposed (VAM and MODI) to determine initial allocation to the basic cells and the corresponding interval transportation cost. The optimal solution is obtained without converting the problem to its classical version. Numerical example is obtained which will be easy to understand the solution and procedure of the proposed method.